Como o marketing verde interfere na imagem da marca da indústria de celulose: o estudo de caso da aracruz celulose - Waissman, Vera (2001)
The purpose of this work, is to analyze the principles underlying the pulp and paper industry, here portrayed by Aracruz Celulose S A, in the marketing standpoint, as far as it concerns being in harmony with nature and adapting its relations with the stakeholders, notably regarding the community of the State of Espírito Santo. As they form, indeed, part of the same discussion, the goal is to proceed with a detailed examination of the major aspects and conditions involved, based in its corporate communications, leading to the construction of a positive corporate brand. The results found throughout this study show that despite Aracruz and the communities¿ different goals, they converge regarding their interests towards the best practices in social and environmental practices, and a more objective communication. Industry and community can work together for a same benefit: the best relations of man towards Nature, and of man towards man. The examples here stated will endorse our perception as well as serve to evaluate the results of the measures adopted in this relationship. It could be verified how internal and external aspects of the organization influence the company¿s reputation, leading to important changes in attitude and in the production process. Pressures from stakeholders have contributed largely in helping Aracruz become more conscious of the important role it plays in the social-environmental universe of the State of Espírito Santo. The assessment of leading the process of communications within in-depth transparency have signaled that, despite a closer approach with its stakeholders, Aracruz still needs to fulfill an existing gap: an excellent rapport between the company and the communities where it influences still needs to be pursued, especially regarding communicating its activities.